2002
DOI: 10.3171/spi.2002.96.2.0168
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of myelopathy in patients with ossification of the posterior longitudinal ligament

Abstract: Study DesignThis was a prospective study with an average 11-year follow-up review. Clinical and radiographic changes in Object. The goal of this study was to clarify the pathogenesis of myelopathy in patients with ossification of the posterior longitudinal ligament (OPLL) based on the relationship between static compression factors and dynamic factors.Methods. There was a total of 247 patients, including 167 patients who were conservatively followed for a mean of 11 years and 2 months and 80 patients who had m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
92
0
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(97 citation statements)
references
References 15 publications
1
92
0
4
Order By: Relevance
“…Matsunaga et al [6] also reported that during the natural course of OPLL in the cervical spine, 37 (22 %) of 167 patients developed or suffered from aggravated spinal symptoms. All patients with less than 6 mm space available for the spinal cord (SAC) suffered from myelopathy, whereas patients with 14 mm or greater did not.…”
Section: Discussionmentioning
confidence: 99%
“…Matsunaga et al [6] also reported that during the natural course of OPLL in the cervical spine, 37 (22 %) of 167 patients developed or suffered from aggravated spinal symptoms. All patients with less than 6 mm space available for the spinal cord (SAC) suffered from myelopathy, whereas patients with 14 mm or greater did not.…”
Section: Discussionmentioning
confidence: 99%
“…Ossification of this ligament is characterized by ectopic bone formation, and is frequently linked with similar ossification in other surrounding spinal ligaments. These ossified lesions often enlarge with time and compress the spinal cord and its roots, leading to neurological deficiencies and a high risk of spinal cord injury [1,2]. Patients with severe symptoms are considered definitive candidates for surgical treatment such as spinal decompression [3].…”
Section: Introductionmentioning
confidence: 99%
“…8,19 As the spinal cord becomes compressed by ossified or hypertrophied ligament and bone spurs, the cushioning effect of CSF is lost. In a series of 200 patients seeking treatment for CSS, 63 (31.5%) reported an episode of minor trauma in the preceding 2 weeks.…”
Section: Pathophysiological Features Of Csm In Opllmentioning
confidence: 99%